Effects of active labour on the ultrastructure of amnion epithelium - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 1998)
The study was conducted at Zeynep Kamil Women and Children's Hospital and Marmara University Department of Histology and Embryology to investigate the effects of active labour on the ultrastructure of amnion epithelium. Among patients between 38 and 41 weeks of gestational age, who were randomly chosen, 15 delivered by elective caesarean section before the onset of labour and 10 delivered after the onset of labour by the normal route or caesarean section. The placenta and membranes were collected from each subject and 1 mm(3) from each was studied by light, transmission and scanning electron microscopy. Some specimens were stained by lipid dyes to determine lipid fractions. In the group without active labour the surface of the epithelium was indented with high collumnar cells. There were numerous microvilli. Scanning electron microscopy showed a polygonal mosaic domed structure. The amnion cells had phospholipid granules in some areas when the specimens were stained by lipid dyes. In the group which had active labour, transmission electron microscopy showed that the amniotic epithelium interchanged between cubic and squamous, there were fewer microvilli, intercellular junctions were looser and the cells contained multiple lipid vesicles. On scanning electron microscopy, there were intercellular fissures with depressions in their centres. The lipid granules were spread diffusely in the amnion cells as shown by lipid dyes. We conclude that the ultrastructural changes in amnion epithelium after the onset of labour suggest it has an active role in triggering the onset of labour. (C) 1998 Chapman & Hall Ltd.
Keywords: active labour; amnion epithelium; HUMAN-FETAL MEMBRANES; PROTEIN-KINASE-C; HUMAN PARTURITION; PROSTAGLANDIN-E; DECIDUA; METABOLISM; BIOSYNTHESIS; INITIATION; TISSUE; CELLS